(untitled) (Redmond, Wash, 2007)
The smart way to learn Microsoft Windows SharePoint Services Version 3.0--one step at a time! Work at your own pace through the easy numbered steps, practice files on CD, helpful hints, and troubleshooting tips to master the fundamentals of working with the latest version of Windows SharePoint Services. You will learn the essentials for creating and managing SharePoint sites and Web Parts, including working with lists and libraries. You'll even discover how to work with collaboration features to create surveys, discussion boards, wikis, and blogs. Plus, you'll learn how to work with Microsoft Office Excel® 2007, Office Access 2007, Office InfoPath® 2007, and Office Outlook® 2007 in Windows SharePoint Services. With STEP BY STEP, you can take just the lessons you need or work from cover to cover. Either way, you drive the instruction, building and practicing the skills you need, just when you need them! Includes a companion CD with hands-on practice files.
Keywords: Intranets (Computer networks),Web servers,Intranets (Mạng máy tính),Dịch vụ Web